Educational environment as the foundation for metasubject competences forming - Nina A. Tymoshchuk (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
The article substantiates the formalization of the learning discipline through the adaptive learning system, which is a model of the modern educational environment, which opens one of the possible ways to digital education. Taking as an example the discipline "Educational and cultural technologies" and its mastering with the help of a textbook and a workbook describes the formation of individuals in general cultural, professional and meta-subject competencies step-by-step by execution of logical schemes of indicative actions based on the cognitive-activity matrix. It is shown that such approach to education makes it possible to individualize the system of professional training of students, to create scientifically grounded educational and methodological computer support of the educational process. An individual who has all the opportunities to achieve the required level of qualifications independently will be able to replenish knowledge and implement his educational project without information support of specially trained people for this purpose; self-education acquires a continuous character; the breadth of basic education will allow you to switch quickly to related areas of professional activity.The metaproject content of educational standards should include not only the real objects of the reality being studied, including fundamental educational objects and general cultural knowledge, including fundamental problems, but also general (meta-subjective) skills, generalized methods of activity and key (meta-subject) educational competence. Key competences (value-semantic, general cultural, educational-cognitive, communicative, informational, social-labor, personal self-improvement) refer to general (meta-subject) content of education. Key competencies are not only meta-subjective and interdisciplinary, they are also multidimensional and multifunctional, they require significant intellectual development - defining their position, critical and abstract thinking, selfesteem, selfreflection, etc.The information presented in the training manuals is written on the basis of modern scientific and theoretical achievements in the field of theory and methodology of professional education, covered mainly in dissertations and periodicals, as well as on the basis vet personal experience of the authors. The multilevel tasks considered in the workbook gradually develop the meta-subject skills of students and give them the opportunity to form not only the above competences, but also to acquire the skills of deep independent study of the subject and organization of their own self-educational activity.